Ultrasound of Optic Nerve Sheath Diameter and Stroke Outcomes. (11th November 2021) - Patel, Rohit; Chowdhury, Muhammad A. B.; Gul, Sarah; Fahy, Brenda G.; Gonzalez, Andres; Fitzpatrick, Desmond; DePortu, Giuliano; Weeks, Emily; Elie-Turenne, Marie-Carmelle; Ocampo, Samirah; Ponnaluri, Sameer; Pizzi, Michael A.
Abstract : Supplemental Digital Content is available in the text. Abstract : OBJECTIVES: We aimed at utilizing ocular ultrasound to determine its utility in predicting outcomes among stroke patients. DESIGN: Single-center prospective observational study. SETTING: Emergency department and ICUs. PATIENTS: Patients suspected of stroke. INTERVENTIONS: None. MEASURES AND MAIN RESULTS: Bilateral optic nerve sheath diameter was measured on arrival and within the first 2 days of admission. Outcomes were inpatient survival, Cerebral Performance Category, and modified Rankin Scale at 3 and 6 months. Analysis was conducted using descriptive statistics, paired t test, chi-square test. Eighty-six patients were enrolled with ischemic or hemorrhagic stroke. Mean age was 67.2 years (± 15 yr), and 54.7% of patients were male. There was no difference between left and right eye measurements ( p = 0.467 and p = 0.903, respectively) or between longitudinal and transverse measurements (transverse p = 0.163 and longitudinal p = 0.270). Mean optic nerve sheath diameter differed in patients who survived versus died prior to discharge in both ischemic (0.53 vs 0.58 cm; p = 0.009) or hemorrhagic stroke (0.57 vs 0.62 cm; p = 0.019). For every 0.1 cm increase in optic nerve sheath diameter, odds ratio for death were 4.2 among ischemic stroke (95% CI, 1.32–13.64; p = 0.015), and odds ratio 6.2 among ischemic or hemorrhagic patients (95% CI, 1.160–33.382; p = 0.033). Increased optic nerve sheath diameter correlated ( r = 0.44; p < 0.0001) with poor functional outcomes measured as modified Rankin Scale scores of 3–6 at 6 months. CONCLUSIONS: Elevations in optic nerve sheath diameter were associated with increased inhospital mortality and poor functional outcome at 6 months. Optic nerve sheath diameter may serve as a noninvasive marker of inhospital mortality and functional outcome. Further multicenter prospective trials for evaluating and treating optic nerve sheath diameter in ischemic and hemorrhagic strokes are warranted.